Project Risk Management in Smaller Software Teams - Crosby, Dave (Auckland University of Technology, 2007)
This thesis investigates project risk management issues in smaller software teams. Certain gaps in the literature are identified. There is limited literature on what risk management techniques software practitioners use. The studies that are published tend to focus on large software teams. This thesis investigates what risks these smaller teams consider to be important. It also investigates what techniques are perceived to address these risks and how effective those techniques are considered to be. One of those risks is found to be of primary importance, yet this risk is not suggested by the project management literature. This thesis goes on to conduct a more in-depth exploration of that specific risk in the context of these smaller teams Interviews were selected as the most appropriate method to achieve the objectives of the thesis. Nineteen interviews in eight software organisations are conducted to collect data for this thesis. Three different perspectives on project risk were investigated. Those were the perspectives of the; service managers, project managers and developers. Hence a large store of rich information is collated. The results are analysed and a rich set of information is presented in this thesis. As a result of this research it is suggested that smaller software teams may find it useful to consider the 16 risks discussed in this research and how applicable those risks are to their individual organisation. Service managers may need to do more to raise the awareness of the importance of risks associated with ‘customer relationship issues’ within their own organisations. Three risks stood out as areas where future research might be most fruitful. They were; customer relationship issues, introduction of new technology and unrealistic schedules and budgets. Risks related to customer relationship issues were of particular significance and have tended to be over looked in the project management literature. It is submitted that research into standard project risk management approaches may need to be combined with business risk management approaches to gain a full understanding of the risks faced and addressed by these smaller teams.
Keywords: Project management; Software project; Small projects; Software development; Risk management